Indo-European cooperation in an interdependent world: an overview and analysis - Knall, Bruno; Veit, Wolfgang (Internationales Asien-Forum, 1988)
The European Community’s attitude towards developing countries was initially determined by a regionalistic approach, resulting in a distinction between associated and non-associated developing countries. For several reasons, the non-associated developing countries - among them India - signed bilateral commercial and cooperation agreements with the European Community (EC). These countries benefit from the Generalized System of Preferences, from specific measures promoting trade and the transfer of capital and technology as well as from development aid and food aid. This indicates that the EC is moving towards a globalistic approach, although the ACP group and the southern Mediterranean countries still make up the inner circle of privileged cooperation. The poor performance of India with respect to her trade with the European Economic Community (EEC) is caused both by the protectionist policies of the EEC and the dirigisme in India in the fields of trade, industry and the public sector. Although attempts towards liberalization were already made after the first oil crisis, reforms have gained special importance since Prime Minister Rajiv Gandhi’s assumption of office. His early drive to free the economy from restrictions is criticized by all those who enjoyed benefits from them. The implemented and projected reforms indicate India’s willingness to reach the level of the newly industrialized countries (NICs). On her way, however, she will face both stiff competition from NICs as well as protectionism from the industrialized countries. Alternatively, therefore, closer economic ties with the neighbouring countries of South Asia are considered. Looking at India’s involvement in world affairs and world politics, India’s relations with the European Community, Japan, USA, USSR and China are surveyed. A positive development of future Indo-EC relations depends mainly on the successful implementation of market-oriented economic strategies by India and a consistent European concept of development and cooperation policy which includes the trade dimension. However, both still seem to be missing. Better coordination of the economic, political and development aspects may be expected if European internal integration comes nearer completion by shifting more competences of the member states towards the EC institutions. Hence, it seems that the Community’s external relations with developing countries must be strongly linked with the EC’s own internal integration. In her own interest, India should support the EC in this endeavour.
Elektronische Reproduktion der Druckausgabe
Keywords: Europäische Gemeinschaften; Indien